An investigation of thermal contact conductance using the lumped parameter method - Chow, J. H. (2013)
Machine structure deformation due to temperature profiles within the material affects the accuracy in precision machines. This can be attributed to the indeterministic temperature distribution in the materials of the machine structure that is caused by the nonlinear heat transfer phenomenon. For machines equipped with linear motors, the copper coil in the motor forcer is the main internal heat source. Heat loss through convection that transfers heat to the surrounding and via contact conductance in between solids interface causes temperature variation in the motor carriage. In order to accurately predict the temperature profile, the contact conductance value used in the thermal model plays an important role. It varies in a wide range in the transient state of the thermal analysis. This work attempts to investigate the variation of contact conductance value in relation to surface temperature, interface pressure and interface interstitial material. It is hoped that the thermal model established in this work can be extended to analyze the thermal characteristics of machine structures with linear stages under thermal loading.